Aesthetic Reception and Interpretation of the Mamaca Oral Tradition in Pamekasan, Madura - Affan, Mohammad; Riyanto, Waryani Fajar; Bin Shuib, Shushilil Azam (Journal of Language and Literature Studies, 2025)
The mamaca tradition, a vibrant form of Islamic oral literature, endures as a living cultural and spiritual expression in Bandaran Village, Pamekasan Regency. This study explores its reception and sustainability using qualitative methods grounded in the aesthetics of literary reception. Data were collected through interviews, observations, and documentation, then analyzed through an interpretive reception framework to uncover how audiences derive meaning from mamaca performances within social and religious contexts. The findings indicate that mamaca is not merely a literary expression but also a medium for moral education, religious contemplation, and the reinforcement of cultural identity. The interactive role of the tokang maca (reciter) and tokang tegghes (interpreter) fosters dialogic engagement between sacred texts and the audience. Through various tembang (verse songs) such as Artate, Kasmaran, Durma, Salangit, Pangkur, and Sinom, audiences reflect on themes of divine love, struggle, spiritual yearning, youthful vigor, and moral virtues rooted in Islamic values. The presence of Arabic loanwords in mamaca exemplifies linguistic Islamization and connects the tradition to the broader Malay-Islamic literary heritage. Functioning as a historical agent of Islamization and a cultural archive, mamaca preserves communal memory and moral instruction akin to syair and hikayat. The study identifies six distinct reception patterns shaped by audiences’ expectations, revealing both passive appreciation and active reinterpretation. This reception-focused lens offers new insights into Islamic oral traditions, highlighting their adaptability, intergenerational transmission, and potential for integration into educational and digital platforms to ensure their relevance in contemporary Muslim societies.